2017
DOI: 10.2139/ssrn.2956442
|View full text |Cite
|
Sign up to set email alerts
|

Flexing the Frame: TMT Framing and the Adoption of Non-Incremental Innovations in Incumbent Firms

Abstract: Why do incumbent firms so frequently reject non-incremental innovations? One reason is due to the firm's top management team's (TMT) lack of frame flexibility, i.e., an inability to expand the organization's categorical boundaries so as to encompass a wider range of emotionally resonate capabilities in the context of innovative change. For incumbent firms, we argue that the way the TMT cognitively thinks about, and emotionally frames, non-incremental innovation and organizational capabilities drives innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 212 publications
(197 reference statements)
0
2
0
Order By: Relevance
“…The managerial cognition literature has shown how the same event can be perceived and framed as an opportunity, threat, both, or even ignored by managers Shepherd, Mcmullen, & Ocasio, 2017;. Raffaelli, Glynn, and Tushman (2017) highlighted the importance of executives' frame flexibility, arguing that the reason for why some firms fail in adopting non-incremental innovations lies at the inability of their executives to frame the innovation within the boundaries of firm's capabilities. They argue that narrow categorizations of firms' capabilities in the minds of executives hinder pursuing non-incremental innovation opportunities.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The managerial cognition literature has shown how the same event can be perceived and framed as an opportunity, threat, both, or even ignored by managers Shepherd, Mcmullen, & Ocasio, 2017;. Raffaelli, Glynn, and Tushman (2017) highlighted the importance of executives' frame flexibility, arguing that the reason for why some firms fail in adopting non-incremental innovations lies at the inability of their executives to frame the innovation within the boundaries of firm's capabilities. They argue that narrow categorizations of firms' capabilities in the minds of executives hinder pursuing non-incremental innovation opportunities.…”
Section: Theorymentioning
confidence: 99%
“…Existing research has shown the benefits of ambidexterity, as well as the barriers that firms face in creating a balance between exploration and exploitation (for reviews see Lavie, Stettner, &Tushman, 2010, and. Despite the importance of ambidexterity for firms' success and the crucial role of managers in enhancing firms' ability to be ambidextrous (Gibson & Birkinshaw, 2004;Hill & Birkinshaw, 2014;Raisch & Birkinshaw, 2008), the characteristics and behaviors of managers that augment ambidexterity are relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%